2020
DOI: 10.1108/ijm-01-2020-0036
|View full text |Cite
|
Sign up to set email alerts
|

Promoting in-role and extra-role green behavior through ethical leadership: mediating role of green HRM and moderating role of individual green values

Abstract: PurposeHuman misbehaviors are responsible for climate change as they waste resources and pollute water and air that dilapidate the environment. Considering the fact and contributing to the United Nations sustainable development goals of 2019, organizations started focusing their green HRM practices to develop employees' green attitudes and behaviors. This study is an attempt in this direction. It examines the impact of ethical leadership on individuals' green in-role and extra-role behaviors with the mediating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
119
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(126 citation statements)
references
References 102 publications
7
119
0
Order By: Relevance
“…Similarly, the implementation of EEB will not be successful unless clear rules and regulations guide employees' actions. The findings are consistent with Lasrado and Zakaria's [76] and Islam et al [91].…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, the implementation of EEB will not be successful unless clear rules and regulations guide employees' actions. The findings are consistent with Lasrado and Zakaria's [76] and Islam et al [91].…”
Section: Discussionsupporting
confidence: 90%
“…Fourth, our research offers a synergistic perspective of the influence of both ethical leadership and GHRM on employees' green behavior (Leroy et al , 2018). As the literature on GHRM is still very limited (Dumont et al , 2017; Guerci, et al , 2016; Islam et al , 2020b; Shen et al , 2016), our research identified ethical leadership as its key antecedent and green behavior as its key outcome. Fifth, our research showed that GHRM mediates the relationship between ethical leadership and employee green behavior, and thus expands knowledge on the mechanisms associated with this leadership style.…”
Section: Discussionmentioning
confidence: 99%
“…The first theoretical contribution of this analysis is the fact that it enriches the existing CSR literature from the perspective of employees, whereas the majority of the previous studies on the present topic have addressed CSR to attain other objectives instead of focusing on employees [45,46,[138][139][140]. Moreover, employees' perception of CSR in the service industry has not been well explored in the available literature, therefore the current analysis is also an important addition to the literature from this perspective, in that that it considers the service sector-most of the previous studies in this connection were carried out in the manufacturing sector [28,138,141]. Similarly, the inclusion of ethical leadership as a mediator in the proposed relationship from the perspective of the banking sector also provides a unique insight into the existing literature on CSR and organizational management.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have also established that ethical leadership (EL) positively impacts employees' behavior [27][28][29]. However, it is somehow not known how ethical leaders may influence their followers' CSR-specific behaviors or, for example, employees' pro-environmental behavior (EB).…”
Section: Introductionmentioning
confidence: 99%